Numerical simulation and experimental investigation of cavity filling in powder injection rapid prototyping process - Liu, Bilon. (2008)
Cavity filling of a powder-binder mixture is a crucial stage in a newly proposed powder injection rapid prototyping (PIRP) and powder injection molding (PIM) processes, in which a metallic or ceramic powder-binder mixture is heated and injected into a mold cavity to create a solid layer of a green part. The essential problem in the cavity filling is the non-homogeneous powder distribution in the green part caused by shear-induced powder migration and flow convection, which may influence dimensional accuracy and mechanical properties of final PIRP parts. The objectives of this study focus on the investigation of flow behavior, heat transfer and powder migration characteristics of cavity filling of a powder-binder mixture.